Minimally ivasive endodontics (Research, Society and Development, 2024)
With the growing concern regarding the resistance of endodontically treated teeth, as well as the restoration of their function, aesthetics, and longevity, the main objective of this article was to conduct a literature review aimed at gathering information and comparing analyses of traditional, conservative, and ultraconservative preparations. Searches were conducted for articles on websites such as Bireme, Scielo, and PubMed to collect information for a literature review. The preservation of dental structure is of great importance for the longevity of endodontically treated teeth. However, some points need to be considered, one of which is the professional's training to ensure the technique is performed correctly, as well as the effective cleaning of the root canal. It was concluded, from this review, that there is little difference between conservative and ultraconservative endodontic access regarding the resistance of the tooth. Moreover, it is necessary to conserve dentin in the cervical portion of the tooth, as this is the most fragile area, presenting a higher fracture rate.